2016
DOI: 10.1186/s12902-016-0133-7
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose acarbose decreased glucose-dependent insulinotropic peptide and glucagon levels in Chinese patients with newly diagnosed type 2 diabetes mellitus after a mixed meal

Abstract: BackgroundAcarbose slows down the intestinal absorption of carbohydrates, but its effects on the secretion of incretins are still poorly known. This study aimed to examine the effects of single-dose acarbose on the secretion of incretins in patients with newly diagnosed type 2 diabetes mellitus (T2DM).MethodsIn this pilot study, twenty-three patients diagnosed with T2DM were randomly assigned to the oral glucose tolerance test (OGTT) group (n = 11) and the mixed meal test (MMT) group (n = 12). Fourteen subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…In our study, all carbohydrates suppressed glucagon secretion with no substantial differences between RYGB and control subjects, and glucagon was not enhanced by distal digestion, suggesting that other mechanisms besides co-secretion with GLP-1 from L-cells are involved (64). Secretory responses of C-peptide were considerably lowered by acarbose in both RYGB and control subjects in agreement with previous reports (30,32,33,49). Reduced beta-cell stimulation by glucose and incretin hormones following alpha-glucosidase inhibition may explain this finding.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, all carbohydrates suppressed glucagon secretion with no substantial differences between RYGB and control subjects, and glucagon was not enhanced by distal digestion, suggesting that other mechanisms besides co-secretion with GLP-1 from L-cells are involved (64). Secretory responses of C-peptide were considerably lowered by acarbose in both RYGB and control subjects in agreement with previous reports (30,32,33,49). Reduced beta-cell stimulation by glucose and incretin hormones following alpha-glucosidase inhibition may explain this finding.…”
Section: Discussionsupporting
confidence: 92%
“…Judging from the glycemic profiles, alpha-glucosidase inhibition by acarbose effectively suppressed sucrose digestion, but somewhat surprisingly, this did not lead to greater GLP-1 secretion in control subjects, again raising doubt about the idea that delaying glucose absorption to distal sites will enhance GLP-1 secretion. Previous studies in unoperated individuals have observed only slightly increased GLP-1 release when acarbose is ingested with sucrose (29,30), and generally no change when the drug is combined with a mixed meal (32)(33)(34)(35)(36). Given that absorption of glucose is necessary for GLP-1 secretion also in the ileum (18), the simplest explanation for the lack of effect is that the alpha glucosidase activity was inhibited so much that hydrolysis was partially prevented, leading to malabsorption and transfer of some of the sucrose load to the colon.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…a-Glucosidase inhibitors (acarbose and miglitol) reduce levels of both GIP and glucagon (15), delay glucose absorption, and thereby blunt the insulin response to glucose (16). DPP-4 inhibitors are known to increase the early insulin response (by increasing circulating concentrations of active GLP-1), reduce glucagon secretion in a glucose-dependent manner, and therefore reduce both hyper-and hypoglycemia.…”
Section: Commentarymentioning
confidence: 99%
“…There are studies that showed that he GIP and glucagon levels decreased after a mixed meal in patients with new diagnosed type 2 diabetics by treatment with single-dose acarbose [36,37] and acarbose decreased GIP and glucagon only in a mixed meal test rather than OGTT. [38] Glitazones Low-dose glitazones given to patients with reactive hypoglycemia associated with IGT are also considered to be effective in the symptoms of reactive hypoglycaemia and the prevention of diabetes. [39,40] As a matter of fact, hyperinsu-linemia and IGT were found in OGTT in 2 cases with hypoglycemic symptoms, and it has been shown that hyperinsulinemic clamp reduces the insulin sensitivity.…”
Section: Alpha Glucosidase Inhibitorsmentioning
confidence: 99%